Review of multisensor data fusion techniques and their application to autonomous underwater vehicle navigation - Loebis, D; Sutton, R; Chudley, J (Journal of marine engineering and technology, 2002)
A key problem with autonomous underwater vehicles is being able to navigate in a generally unknown environment. The available underwater sensor suites have a limited capability to cope with such a navigation problem. In practice, no single sensor in the underwater environment can provide the level of accuracy, reliability and the coverage of information necessary to perform underwater navigation. Therefore there is a need to use a number of sensors and combine their information to provide the necessary navigation capability in a synergetic manner. This may be achieved by employing multisensor data fusion (MSDF) techniques and these are the subject of the material presented in this paper.